Β-Hydroxybutyric acid upregulated by Suhuang antitussive capsule ameliorates cough variant asthma through GSK3β/AMPK-Nrf2 signal axis. (10th May 2023) - Jiang, Hong; Bai, Ziyu; Ou, Yongyu; Liu, Huiling; Si, Zilin; Liu, Yafang; Liu, Xiaoqiong; Liu, Xiaoqing; Zhang, Zhihao; Tan, Ninghua
Abstract: Ethnopharmacological relevance: Cough variant asthma (CVA) is a chronic inflammatory disease characterized by cough as the main symptom. Suhuang antitussive capsule (Suhuang), one of traditional Chinese patent medicines, mainly treats CVA clinically. Previous studies have shown that Suhuang significantly improved CVA, post-infectious cough (PIC), sputum obstruction and airway remodeling. However, the effect of Suhuang on ovalbumin-induced (OVA-induced) metabolic abnormalities in CVA is unknown. Aim of the study: This study aimed to identify potential metabolites associated with efficacy of Suhuang in the treatment of CVA, and determined how Suhuang regulates metabolites, and differential metabolites reduce inflammation and oxidative stress. Materials and methods: Rats were given 1 mg OVA/100 mg aluminum hydroxide in the 1st and 7th days by intraperitoneal injection and challenged by atomizing inhalation of 1% OVA saline solution after two weeks to establish the CVA model. Rats were intragastrically (i.g.) administrated with Suhuang at 1.4 g/kg and β-hydroxybutyric acid (β-HB) were given with different concentrations (87.5 and 175 mg/kg/day) by intraperitoneal injection for 2 weeks. After 26 days, GC-MS-based metabolomic approach was applied to observe metabolic changes and search differential metabolites. The number of coughs, coughs latencies, enzyme-linked immunosorbent assay (ELISA), histological analysis and quantitative-polymerase chain reaction (Q-PCR) were used to investigate the effects of Suhuang. Then β-HB on CVA rats, NLRP3 inflammasome and GSK3β/AMPK/Nrf2 signalling pathway were detected by western blotting. Results: The results showed that Suhuang treatment significantly enhanced the serum level of β-HB. Interestingly, exposure to exogenous β-HB was also protective against OVA-induced CVA. β-HB significantly reduced the number of coughs and lengthened coughs latencies, improved lung injury, reduced the secretion of various cytokines, and directly inhibited the NLRP3 inflammasome. In addition, β-HB increased the nuclear accumulation of Nrf2 by activating the GSK3β/AMPK signaling axis, and then inactivating the NF-κB signaling pathway, effectively protecting OVA-induced CVA from oxidative stress and inflammation. Conclusions: The results of this study shows that β-HB can reduce inflammation and oxidative stress, the increased production of β-HB in serum might be the crucial factor for Suhuang to exert its effect in the treatment of CVA. Graphical abstract: Image 1 Highlights: Suhuang treatment significantly increases the serum level of β-hydroxybutyric acid (β-HB). β-HB protects against cough variant asthma (CVA) in vitro and in vivo. β-HB ameliorates CVA by regulation of GSK3β/AMPK-Nrf2 signal axis and NLRP3 inflammasome.